2015
DOI: 10.1016/j.ijid.2015.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic foot infections: what have we learned in the last 30 years?

Abstract: The worldwide increase in the incidence of diabetes and longer lifespan of diabetic patients will undoubtedly increase the incidence of DFIs. Clinicians caring for diabetic patients should have an understanding of current methods for preventing, diagnosing, and treating DFIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
147
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(155 citation statements)
references
References 145 publications
(156 reference statements)
4
147
0
4
Order By: Relevance
“…A study by Tiwari et al, (2012) reported exactly similar figure of 68% gram negative bacilli and 32% gram positive cocci from 82 strains isolated from 62 patients with infected diabetic foot ulcer. Some of the possible reasons cited for this discrepancy include hot climate causing foot sweating, unfitting footwear, frequent foot washing and the suboptimal perineal/hand hygiene (Uckay et al, 2015;Ramakant et al, 2011) The Escherichia coli, 38 out of 173 total isolates (21.96%) was the predominant organism identified followed by Klebsiella spp (31 out of 173, 17.92%) in this study. The study by Esmat et al, (2012) had reported similar results.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…A study by Tiwari et al, (2012) reported exactly similar figure of 68% gram negative bacilli and 32% gram positive cocci from 82 strains isolated from 62 patients with infected diabetic foot ulcer. Some of the possible reasons cited for this discrepancy include hot climate causing foot sweating, unfitting footwear, frequent foot washing and the suboptimal perineal/hand hygiene (Uckay et al, 2015;Ramakant et al, 2011) The Escherichia coli, 38 out of 173 total isolates (21.96%) was the predominant organism identified followed by Klebsiella spp (31 out of 173, 17.92%) in this study. The study by Esmat et al, (2012) had reported similar results.…”
Section: Resultsmentioning
confidence: 65%
“…In temperate and western countries the aerobic gram positive cocci, Staphylococcus aureus is the predominant organism isolated often methicillin resistant in recent times. In warm subtropical countries like India, many studies reported mixed polymicrobial infection with the predominant organisms being aerobic gram negative bacilli such as Enterobactericeae, Pseudomonas aeruginosa (Uckay et al, 2015;Ramakant et al, 2011). Bacteroides fragilis, Peptostreptococcus spp., are some of the frequently implicated obligate anaerobic bacteria in the infection of diabetic foot ulcer (Halpati et al, 2014).…”
Section: International Journal Of Current Microbiology and Applied Scmentioning
confidence: 99%
See 1 more Smart Citation
“…Glisemik kontrolün sağlanamadığı olgularda, hemoglobin A1c seviyesindeki yüksekliğin de diyabetik ülser gelişimi ve yara iyileşmesindeki gecikmeyle olan yakın ilişkisi de bilinmektedir (5). Tedavisi multidisipliner olup, enfeksiyon hastalıkları, cerrahi, vasküler cerrahi, ortopedi gibi pek çok kliniğin multidisipliner yaklaşımını gerektirir (6).…”
Section: Introductionunclassified
“…Antibiyotik tedavisi yanında cerrahi debridman, yara bakımı ve hiperbarik oksijen (HBO) tedavisi gibi, maliyeti yüksek, yönetimi zor ve tedavi şansı düşük yardımcı tedavi yöntemleri de denenmektedir (4,(6)(7)(8). Bu tedavilerle hastane maliyetleri artmakta, yatak işgal süresi uzamakta ve bu konuda deneyimli personel ihtiyacı da ayrı bir problem olarak karşımıza çıkmaktadır.…”
Section: Introductionunclassified